Secondary Ion Mass Spectrometry Bias on Isotope Ratios in Dolomite–Ankerite, Part II: δ13C Matrix Effects. Issue 2 (20th November 2015) - Śliwiński, Maciej G.; Kitajima, Kouki; Kozdon, Reinhard; Spicuzza, Michael J.; Fournelle, John H.; Denny, Adam; Valley, John W.
Abstract : This study is Part II of a series that documents the development of a suite of calibration reference materials for in situ SIMS analysis of stable isotope ratios in Ca‐Mg‐Fe carbonates. Part I explored the effects of Fe 2+ substitution on SIMS δ 18 O bias measured from the dolomite–ankerite solid solution series [CaMg(CO3 )2 –CaFe(CO3 )2 ], whereas this complementary work explores the compositional dependence of SIMS δ 13 C bias (calibrated range: Fe# = 0.004–0.789, where Fe# = molar Fe/(Mg+Fe)). Under routine operating conditions for carbonate δ 13 C analysis at WiscSIMS (CAMECA IMS 1280), the magnitude of instrumental bias increased exponentially by 2.5–5.5‰ (session‐specific) with increasing Fe‐content in the dolomite structure, but appeared insensitive to minor Mn substitution [< 2.6 mole % Mn/(Ca+Mg+Fe+Mn)]. The compositional dependence of bias (i.e., the matrix effect) was expressed using the Hill equation, yielding calibration residual values ≤ 0.3‰ relative to CRM NBS‐19 for eleven carbonate reference materials (6‐μm‐diameter spot size measurements). Based on the spot‐to‐spot repeatability of a drift monitor material that 'bracketed' each set of ten sample‐spot analyses, the analytical precision was ± 0.6–1.2‰ ( 2s, standard deviations). The analytical uncertainty for individual sample analyses was approximated by combining the precision and calibration residual values (propagated in quadrature), suggesting an uncertainty of ± 1.0–1.5‰ (2 s ). Key Points: Calibration of matrix effects (instrumental bias) in the analysis of δ 13 C by secondary ion mass spectrometry from carbonate mineral compositions of the dolomite‐ankerite solid solution. Suite of reference materials developed and documented. The matrix effect changes exponentially with increasing Fe‐content in the dolomite crystal structure (using a CAMECA IMS 1280 instrument).